The shifting philosophy behind the protected area concept and its applicability in the South African context - Cryer, Paul; Procheş, Şerban; Druce, Dave J. (Frontiers in Conservation Science, 2024)
The necessity of increasing biodiversity conservation efforts has been highlighted by planetary boundary research. Through review and critical thinking, this paper aims to highlight inadequacies within historic and current environmental ideologies, many of which continue to entrench flawed conservation trajectories. The first part of this paper reviews the context in which the term conservation has been viewed within society, particularly between 1950 and the present day, revealing an early preservationist purpose that was embedded within a larger context of environmental plunder. It examines differing social, scientific and economic dimensions as well as certain approaches to environmental awareness within that period, particularly as it applies to the historic and emerging value of protected areas. It does this through the lenses of divergent thinking, including sequential iterations of colonialism, neoliberalism, “new conservation”, convivial conservation and ecocentrism. By juxtaposing the gradual increase in environmental awareness with socio-political and economic milestones within the last 70 years, it illustrates why firstly, truly reformist thinking has not gained traction and secondly, why exploitative and inherently unsustainable forms of environmentalism have endured within policy. By illuminating these factors, the duplicity of certain conservation trajectories is exposed. Contrastingly, some unlikely alliances between previously antagonistic socio-environmental ideologies are introduced. The second part of the paper deals with how emerging environmental principles are being applied (or not) within South Africa’s proud conservation history. It asserts that the post-Apartheid transformation within the environmental sector was incomplete, resulting in the retention of both social and environmental exploitation within policy. With the perpetuation of inadequate measures to stem global (and local) biodiversity loss, despite its now obvious need, the paper concludes with a set of actionable recommendations that have general application to conservation policy makers, researchers and practitioners including those within the South African context. The urgency of addressing the transgressed biodiversity planetary boundary, amidst inertia preventing rectification, provides the motivation underpinning this paper.